2022
DOI: 10.3390/jpm12061013
|View full text |Cite
|
Sign up to set email alerts
|

Two Genetic Mechanisms in Two Siblings with Intellectual Disability, Autism Spectrum Disorder, and Psychosis

Abstract: Intellectual disability (ID) and autism spectrum disorder (ASD) are complex neurodevelopmental disorders with high heritability. To search for the genetic deficits in two siblings affected with ID and ASD in a family, we first performed a genome-wide copy number variation (CNV) analysis using chromosomal microarray analysis (CMA). We found a 3.7 Mb microdeletion at 22q13.3 in the younger sister. This de novo microdeletion resulted in the haploinsufficiency of SHANK3 and several nearby genes involved in neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Deletion of both alleles did not further exacerbate the phenotype. These results reveal that Klhl17 haploinsufficiency impairs activity-dependent dendritic spine enlargement, consistent with genetic features of patients in which only 1 allele of the Klhl17 gene is mutated or deleted [2,14,26].…”
Section: Plos Biologysupporting
confidence: 78%
See 1 more Smart Citation
“…Deletion of both alleles did not further exacerbate the phenotype. These results reveal that Klhl17 haploinsufficiency impairs activity-dependent dendritic spine enlargement, consistent with genetic features of patients in which only 1 allele of the Klhl17 gene is mutated or deleted [2,14,26].…”
Section: Plos Biologysupporting
confidence: 78%
“…Among the various ASD-associated genes, Kelch-like protein 17 (KLHL17), also known as actinfilin [11,12], has been shown to contribute to dendritic spine enlargement during development [13]. Klhl17 +/mice exhibit social deficits and hyperactive locomotion [13], echoing genetic evidence from patients that Klhl17 deficiency is associated with ASD [2,14]. Since KLHL17 controls dendritic spine enlargement, this protein may serve as a model to explore how morphological plasticity is relevant to ASD etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental disorders have variable phenotype expression and heterogenetic pathways which make it challenging for clinicians and geneticists to diagnose. With advent of modern technology involving CMA and genome-wide CNV analysis, Cytoscan HD array is considered as first-tier test for diagnosis of neurodevelopmental disorders with more than 99% accuracy [ 44 ]. Despite these facts, a large number of neurodevelopmental and neuropsychiatric families genetic outlook is missing.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes identified using a relaxed p-value threshold, two genes were confirmed related to brain development and neurodevelopment. In a genetic study involving intellectual disability, autism and psychosis, ATP10A was identified as a gene that may affect neurodevelopmental disorders [22]. Therefore, we investigated these genes to explore their association with dementia.…”
Section: Snpidmentioning
confidence: 99%